Thyroid Surgery in a Resource-Limited Setting: Feasibility and Analysis of Short- and Long-term Outcomes. (March 2017) - Jafari, Aria; Campbell, David; Campbell, Bruce H.; Ngoitsi, Henry Nono; Sisenda, Titus M.; Denge, Makaya; James, Benjamin C.; Cordes, Susan R.
Objective: The present study reviews a series of patients who underwent thyroid surgery in Eldoret, Kenya, to demonstrate the feasibility of conducting long-term (>1 year) outcomes research in a resource-limited setting, impact on the quality of life of the recipient population, and inform future humanitarian collaborations. Study Design: Case series with chart review. Setting: Tertiary public referral hospital in Eldoret, Kenya. Subjects and Methods: Twenty-one patients were enrolled during the study period. A retrospective chart review was performed for all adult patients who underwent thyroid surgery during humanitarian trips (2010-2015). Patients were contacted by mobile telephone. Medical history and physical examination, including laryngoscopy, were performed, and the SF-36 was administered (a quality-of-life questionnaire). Laboratory measurements of thyroid function and neck ultrasound were obtained. Results: The mean follow-up was 33.6 ± 20.2 months after surgery: 37.5% of subtotal thyroidectomy patients and 15.4% of lobectomy patients were hypothyroid postoperatively according to serologic studies. There were no cases of goiter recurrence or malignancy. All patients reported postoperative symptomatic improvement and collectively showed positive pre- and postoperative score differences on the SF-36. Conclusion: Although limited by a small sample size and the retrospective nature, our study demonstrates the feasibility of long-term surgical and quality-of-life outcomes research in a resource-limited setting. The low complication rates suggest minimal adverse effects of performing surgery in this context. Despite a considerable rate of postoperative hypothyroidism, it is in accordance with prior studies and emphasizes the need for individualized, longitudinal, and multidisciplinary care. Quality-of-life score improvements suggest benefit to the recipient population.